Hypoglossal Nerve Stimulation in the Treatment of Obstructive Sleep Apnea: Patient Selection and New Perspectives - Baptista PM (Dove Medical Press, 2020)
Peter M Baptista,1 Andrea Costantino,2 Antonio Moffa,3,4 Vittorio Rinaldi,3 Manuele Casale3 1Department of ORL, Clínica Universidad de Navarra, Pamplona, Spain; 2Otorhinolaryngology Unit, Humanitas Clinical and Research Center-IRCCS, Milan, Italy; 3Department of Otolaryngology, Integrated Therapies in Otolaryngology, University Campus Bio-Medico, Rome, Italy; 4Department of Otolaryngology, University of Foggia, Foggia, ItalyCorrespondence: Peter M BaptistaDepartment of ORL, Clinica Universidad de Navarra, Pamplona, SpainEmail pmbaptista@unav.esAbstract: Hypoglossal nerve stimulation (HNS) is an increasingly widespread OSA treatment. It is a non-anatomical modifying surgery able to achieve an adequate objective and subjective result with a reasonable complication rate. HNS exploits the neurostimulation to reduce upper airway collapsibility providing a multilevel upper airway improvement within a single procedure. Proper patient selection has a fundamental role in determining an adequate long-term clinical outcome. All patient candidates for HNS undergo a standard comprehensive sleep medicine assessment and upper airway surgical examination. Several features should be assessed preoperatively in order to predict patients’ response to HNS treatment. In particular, the assessment of OSA severity, BMI > 32 Kg/m2, collapse pattern during drug-induced sleep endoscopy (DISE), and many other parameters, is central for a good patient selection and customization of OSA treatment. HNS is indeed one of the most promising tools in the widespread context of personalized sleep medicine. HNS is an adjustable medical device that could be titrated in order to improve HNS effectiveness, maintaining patient comfort. Moreover, HNS provides the opportunity for patients to play an active role in their own care, with a potential improvement in therapy adherence and efficacy. This review summarizes the current evidence in patient selection for HNS, highlighting the reasons behind the optimistic future of this OSA treatment in the context of personalized medicine.Keywords: obstructive sleep apnea, hypoglossal nerve, upper airway, stimulation, personalized medicine